Glial cell-derived neuroregulators control type 3 innate lymphoid cells and gut defence - García Cassani, Bethania (2017)
Tese de doutoramento, Ciências Biomédicas (Imunologia), Universidade de Lisboa, Faculdade de Medicina, 2017